Elevated Risk of Bacterial Vaginosis Among Users of the Copper Intrauterine Device: A Prospective Longitudinal Cohort Study. (6th June 2020) - Peebles, Kathryn; Kiweewa, Flavia M; Palanee-Phillips, Thesla; Chappell, Catherine; Singh, Devika; Bunge, Katherine E; Naidoo, Logashvari; Makanani, Bonus; Jeenarain, Nitesha; Reynolds, Doerieyah; Hillier, Sharon L; Brown, Elizabeth R; et al.
Abstract: Background: Limited evidence suggests that the nonhormonal contraceptive copper intrauterine device (Cu-IUD) may increase bacterial vaginosis (BV) risk, possibly due to increased volume and duration of menses, a common side effect of Cu-IUD use. Although increases in bleeding typically resolve within 6–12 months following initiation, evaluations of the association between Cu-IUD and BV have not included more than 6 months of follow-up. Methods: This secondary analysis of a human immunodeficiency virus type 1 prevention trial included 2585 African women ages 18–45 followed for up to 33 months. Women reported contraceptive use each month. BV was evaluated by Nugent score in 6-monthly intervals and, if clinically indicated, by Amsel criteria. Andersen-Gill proportional hazards models were used to (1) evaluate BV risk among Cu-IUD users relative to women using no/another nonhormonal contraceptive and (2) test changes in BV frequency before, while using, and following Cu-IUD discontinuation. Results: BV frequency was highest among Cu-IUD users at 153.6 episodes per 100 person-years (95% confidence interval [CI]: 145.2, 162.4). In adjusted models, Cu-IUD users experienced 1.28-fold (95% CI: 1.12, 1.46) higher BV risk relative to women using no/another nonhormonal contraception. Compared to the 6 months prior to initiation, BV risk was 1.52-fold (95% CI: 1.16, 2.00) higher in the first 6 months of Cu-IUD use and remained elevated over 18 months of use ( P  < .05). Among women who discontinued Cu-IUD, BV frequency was similar to pre-initiation rates within 1 year. Conclusions: Cu-IUD users experienced elevated BV risk that persisted throughout use. Women and their providers may wish to consider BV risk when discussing contraceptive options. Abstract : In this prospective cohort analysis, women using copper intrauterine device (Cu-IUD) contraception experienced 1.28-fold ( P  < .001) elevated risk of bacterial vaginosis (BV). This elevated risk persisted through 18 months of use ( P  < .05) and declined to pre-initiation risk levels following Cu-IUD discontinuation.